Molecular modelling, Synthesis and Antiproliferative Evaluation of New Phenyldiazenyl)-Pyrazol Schiff Base Derivatives - duha emad taha; Monther F. Mahdi; Ayad M. R. Raauf (College of Pharmacy / Mustansiriyah University, 2024)
Lung cancer is the most prevalent worldwide. In addition, it is also the most common cause of cancer-related deaths worldwide, with around 1.8 million new cases annually. With a 5-year survival rate of fewer than 20%. Cytotoxic medicines are commonly employed in cancer treatment. Although the medicine improves patients' quality of life, several disadvantages diminish its efficacy. This necessitates developing new effective strategies that target tumors with minimal adverse effects. This research aims to overcome these issues by synthesizing a new series of phenyldiazenyl)-pyrazol schiff base derivatives by utilizing the molecular docking (GOLD) suite program and the pharmacokinetic properties determination by utilizing (Swiss) ADME suite; The most appropriate-fitting compounds were subsequently produced and confirmed using spectrum analysis (FTIR, 1HNMR, and 13 CNMR). MTT in vitro assay were performed to assess of antiproliferative activities against A549 lung cancer cell lines. The antiproliferative study showed that compound 3a had an inhibitory concentration (IC50 of 17.37 µM) on lung cancer cells (A549), which was significantly higher inhibitory activity than Erlotinib (IC50 = 25.06 µM). While compound 3b had an inhibitory activity comparable to the reference drug's, The IC50 values for compounds 3c, 3d, and 3e were 47.48, 45.56, and 33.05 µM, respectively